The Catabolism of Purine Nucleotides in Liver of Rats With Hypertension Induced By Nitric Oxide Synthase Inhibition - Fadıllıoğlu, Ersin; Erdoğan, Hasan; Emre, Memet Hanifi (Fırat University, 2003)
Aim: Liver is the main metabolic organ in the living organism and may be affected from arterial hypertension. Nitric oxide synthase (NOS) inhibition was shown to produce hypertension in rats. Thus, the aim of this study was to investigate adenosine deaminase (ADA) and xanthine oxidase (XO) activities of liver tissue in rats after chronic NOS inhibition by N sup omega Nitro-L-Arginine Methyl Ester (L-NAME). Material and method: Rats were divided into three groups; the first one was the control group and the others were study groups treated with 100 or 500 mg/L L-NAME in drinking water for 15 days. After above-mentioned treatment, arterial blood pressure was measured via carotid artery cannula on anaesthetised rats. Activities of ADA and XO were carried out in the liver tissue. Results: ADA and XO activities of hypertensive groups were increased significantly compared with control group. There was no significant difference in ADA and XO activities between 100 mg and 500 mg L-NAME groups. Conclusion: Hypertension induced by chronic NOS inhibition may affect purin catabolism and result in high XO and ADA activities.

Amaç: Karaciğer canlı organizmada temel metabolik organdır ve arteryal hipertansiyondan etkilenebilir. Nitrik oksit sentaz (NOS) inhibisyonunun sıçanlarda hipertansiyon oluşturduğu gösterilmiştir. Bu çalışmanın amacı N sup omega Nitro-L-Arjinin Metil Ester (L-NAME) ile kronik NOS inhibisyonu sonrası sıçanlarda karaciğer dokusu adenozin deaminaz (ADA) ve ksantin oksidaz (XO) aktivitelerini araştırmaktı. Gereç ve yöntem: Sıçanlar üç gruba ayrıldı; birincisi kontrol grubu ve diğerleri 15 gün süreyle içme sularında 100 yada 500 mg/L L-NAME uygulanan çalışma gruplarıydı. Uygulanan tedavi sonrası, arteryal kan basıncı karotid arter kanülasyonu ile anestezi uygulanmış sıçanlarda ölçüldü. ADA ve XO aktiviteleri karaciğer dokusunda çalışıldı. Bulgular: Hipertansif gruplarda ADA ve XO aktiviteleri kontrol grubuna göre anlamlı olarak arttı. ADA ve XO aktivitelerinde 100 ve 500 mg L-NAME uygulanan gruplar arasında belirgin fark yoktu.Sonuç: Kronik NOS inhibisyonu ile indüklenen hipertansiyon pürin katabolizmasını etkileyebilir ve yüksek XO ve ADA aktiviteleri ile sonuçlanır.
Nitrik Oksit Sentaz İnhibisyonu ile Hipertansiyon İndüklenen Sıçanların Karaciğerinde Pürin Nükleotidlerinin Katabolizması